Micromechanical mass sensors for biomolecular detection in a physiological environment - HEGNER, MARTIN (My University, 2005)
Micromechanical cantilever arrays are used to measure time-resolved adsorption of tiny masses based on protein-ligand interactions. Here, streptavidin-biotin interactions are investigated in a physiological environment. A measurement method is introduced using higher flexural modes of a silicon cantilever in order to enhance the sensitivity of mass detection. Modeling the cantilever vibration in liquid allows the measurement of absolute mass changes. We show time-resolved mass adsorption of final 7?0.7 ng biotinylated latex beads. The sensitivity obtained is about 2.5 pg/Hz measuring at a center frequency of 750 kHz.
PUBLISHED
Keywords: Physics